PENERAPAN SMART SCHOOL BELL BERBASIS INTERNET OF THINGS DI SDIT CENDEKIA PURWAKARTA - Dzikri Danuarteu, Muhamad; Raina Nurtsania, Santy; Amini Fatihah, Laisya; Saputri, Gais; Makhalingga Ridhwan, Dhaafin; Audia Rossanti, Shafrina; Gin Ginanjar, Gin; Ash Shiddiq, Reza Nurfaudzan; Setyowati, Endah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This research is about the implementation of Smart School Bell based on the Internet of Things (IoT) with the aim of increasing the effectiveness of communication at IT Cendekia Elementary School. The background of this research arises from general problems related to the use of school bells that are still manual and less effective in conveying information to students and teachers. By utilizing the concept of IoT, this research develops a Smart School Bell that is automated and connected online. This research consists of three main stages, namely Pre-Input, Process, and Output. In the Pre-Input stage, the project concept was designed and a survey was conducted to SDIT Cendekia to understand partner needs. The Process stage includes the design and manufacture of the Smart School Bell tool, as well as setting the bell schedule automatically. At the Output stage, this project produces a school bell system that functions automatically with a human voice, increasing the efficiency of the learning process at school. Evaluation results obtained from filling out questionnaires by SDIT Cendekia educators show that the implementation of Smart School Bell has succeeded in increasing the effectiveness of communication at school with an average rating of 4,73 or very good.